Analysis of the Thai Venture Capital industry : development and constraints - Chastel, Germain; Venkatesh, Sundar; Donyaprueth Krairit; Sununta Siengthai (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Venture Capital (VC) is increasingly developing in Asia. However, Thailand{u2019}s VC industry does not seem to undergo the same development as other Asian emerging countries. This research assesses the level of development of the Thai Venture Capital industry by comparing it first to the United States model, and then to other Asian economies. The research then attempts to define some constraints to the development of the industry by studying the development policies implemented by the government, and the actions taken by the Thai Venture Capital Association. Through two case-studies and three interviews, the research finally defines some specificities of the Thai Venture Capital Industry, and shows how Thai funds have developed some practices that give them a competitive advantage over the traditional funds in the Thai context.The research concludes on the distinct structure of the Thai VC industry and the opportunity cost of its underdevelopment.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Business
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2008
Keywords: Venture capital -- Thailand